The Reception of The Prophet Yusuf and His Family: Analyzing of Yusuf Verses 99-100 of Martin Heidegger's Hermeneutic Perspective: RESEPSI NABI YUSUF DAN KELUARGANYA: ANALISIS SURAT YUSUF AYAT 99-100 PERSPEKTIF HERMENEUTIKA MARTIN HEIDEGGER - Nur Ikhlas; Sihabussalam Sihabussalam (Takwil: Journal of Quran and Hadith Studies, 2022)
The story of the Prophet Yusuf (AS) is one of the stories narrated by the Qur'an, even specified in a full Surah, namely Surah Yusuf. In it, there is an event that is evidence of Yusuf's greatness related to dream interpretation which is proven by his reception with his family in Egypt. Surah Yusuf verses 99 and 100 are two verses that describe the story. Understanding these two verses with Martin Heidegger's hermeneutics basically gives a new face regarding the secret of the reception, as well as understanding this phenomenon through Heidegger's concept of phenomenology. With qualitative data and analyzed using Heidegger's hermeneutics, this paper answers the question, how does Heidegger's hermeneutics read the Surah Yusuf verses 99 and 100. As a result, the expression of the reception between the prophet Yusuf and his family was natural and certain; and the terms Abawaihi, Al-'arsy, and Sajada are representations of the sacredness of the reception.